3-MONOKLORO-1,2-PROPANDIOL PADA KEMASAN KERTAS DUPLEKS SERTA MIGRASINYA KE DALAM SIMULAN PANGAN - Ira Dwi Rachmani; Feri Kusnandar; Nancy Dewi Yuliana; Yane Regina; Muh. Yusram Massijaya; Slamet Budijanto (Jurnal Teknologi dan Industri Pangan, 2015)
3-Monochloro-1,2-propandiol (3-MCPD) is a carcinogenic food contaminant. 3-MCPD is formed during food processing, and can also be derived from food contact packaging materials, including paper. Wet-strength resin is often added into paper food packaging to provide moisture resistance and thus enhancing food shelf-life and consumer usage. The wet-strength resins which are manufactured from epichlorohydrin-based starting materials, are known to initiate the formation of 3-MCPD. Thus, the objectives of this study were: 1) to validate an analytical method for the analysis 3-MCPD in duplex paper packaging, 2) to analyze3-MCPD content in duplex paper, and 3) to analyze 3-MCPD migration from duplex paper packaging into food simulants. 3-MCPD content in duplex paper was analyzed by a validated GC-MS method with linearity value (R2) of 0.993, limit of detection (LOD) of 6.65 ppb, limit of quantification (LOQ) of 22.15 ppb, and recovery range of 83.00–114.13%. The 3-MCPD content of five sample duplex papers obtained from different packaging paper manufacturers were ranging from 753.43 to 825.36 ppb, and there was no significant differences between the samples. Direct contact between food simulants and duplex paper for 24 hours at 40°C generated migration of 3-MCPD at levels of 40.55 to 57.61%.